The effect from elimination mechanism on information diffusion on entertainment programs in Weibo - Xu, Nannan; Lin, Qiaoting; Hu, Haibo; Li, Ying (Frontiers in Physics, 2022)
Information diffusion in social media has attracted the wide attention of scholars from diverse disciplines. In real life, many offline events can cause online diffusion of relevant information, and the relation between the characteristics of information diffusion and offline events, as well as the diffusion differences corresponding to different phases of offline events have been studied. However, the effects of offline events on information diffusion are not well explored. In this paper, we study the influence of a popular and multi-phase talent show with elimination mechanism on relevant information diffusion. We find that elimination mechanism has significant influence on the features of information diffusion, and elimination results have a negative effect on followers’ emotional tendency. Elimination results also significantly affect the topics discussed by users. Besides elimination results have a negative effect on participants’ popularity, but do not affect the followers’ loyalty to program participants. This study not only reveals the effects of offline events on online information diffusion, but also provides approaches for studying the online diffusion of similar offline events.